WASIAT RENUNGAN MASA-PENGALAMAN BARU KARYA HAMZANWADI: PRAGMATISME PUISI LAMA PADA ERA MODERN MENURUT CULTURAL STUDIES - Nahdi, Khirjan; Wijaya, Herman; Taufiq, Muh; Yunitasari, Dukha (Universitas Hamzanwadi, 2020)
Pragmatism could be understood as an approach whose position is equal to the other approaches in literary studies. Pragmatism focussed discussion on the role and readers functin totally. Cultural studies has to do with the whole aspects of human?s life as a method to undertand cultural changes and its effect in social life. The Text of Wasiat Renungan Masa-Pengalaman Baru as literary objection this research was understood in cultural changes and the previous phenomenon was a prat of field discusiion of cultural studies wich could be done by decoding organic structure which shapes it (diction), function (das sein=reality), and the meaning (das sollen=idealisme). Research data ws collected trough transcription tehnique because the text of Renungan Masa-Pengalaman Baru is a lingual symbol (forms) to understand meaning and function. Analysis and data interpretation used phenomenology approach. It was conclued that the pragmatism of Wasiat Renungan Masa-Pengalaman Baru composed by Hamzanwadi was understood through pattern realtions function and meaning. Culture decentring was someone?s emotion expression to keep expectation to one he loves, communication for a reality which have to be faced, satire toward unconciousness on life reality. Pragmatism constituted idea guidance and good deeds, direction and goal of noble strugle, warning to the unappropriate events, inspirations the new appropriate one, basic and good behaviour standard in choosing and selecting life struggle instruments. Key words: Wasiat Renungan Masa-Pengalaman Baru, Pragmatism, Culture Studies